Renin-angiotensin and endothelin systems in patients post takotsubo syndrome. (3rd October 2022) - Khan, H; Rudd, A; Gamble, D; Mezincescu, A M; Cheyne, L; Horgan, G; Dhaun, N; Newby, D E; Dawson, D K
Abstract: Background: We investigate if renin-angiotensin and endothelin-1 response pathways follow the same pattern of recovery as left ventricular ejection fraction in patients with takotsubo syndrome. Purpose: To provide better insight into the pathophysiology underlying this condition. Methods: Ninety takotsubo syndrome patients [n=30 in each of "acute", "convalescent" (3–5 months) and "recovered" (>1 year) groups] who were on minimal or no medication and were free of any significant cardiac/metabolic co-morbidities, and 30 healthy controls were studied. Serum concentrations of renin, angiotensin converting enzyme, angiotensin II, big endothelin-1, endothelin-1 were measured using commercially available ELISA, and BNP was measured using an immunoassay. Results: Left ventricular ejection fraction was 38±1.6% in acute, 63±2.0% in convalescent and 64±2.6% in recovered takotsubo syndrome patients. As shown in Figure 1, serum renin concentrations are persistently elevated after a takotsubo episode (p=0.03 vs controls). Angiotensin converting enzyme levels are significantly depressed during the acute phase compared to convalescent (p=0.004), recovered takotsubo (p=0.02) or controls (p=0.03). Angiotensin II is increased in takotsubo patients (p<0.001 vs controls) remaining persistently elevated long-term in the recovered group (p=0.03 vs controls). B-type natriuretic peptide concentrations remain elevated after a Takotsubo episode compared to controls (p=0.003). Big endothelin-1 levels are unchanged, but endothelin-1 is significantly lower after takotsubo syndrome compared to controls (p=0.03). Conclusions: Despite "normalisation" of the left ventricular ejection fraction, there is long-term maladaptive activation of renin-angiotensin system in takotsubo syndrome patients. This suggests therapy aimed at modulating this pathway may be beneficial in the long-term. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): British Heart Foundation